Low Dose Rivaroxaban for Atherosclerotic Cardiovascular Diseases: A Systematic Review and Meta-analysis - Chen, Can; Kan, Yuanqing; Shi, Zhenyu; Guo, Daqiao; Fu, Weiguo; Li, Yanli; Lv, Qianzhou; Li, Xiaoyu; Si, Yi (Frontiers in Pharmacology, 2021)
Background: This study aims to explore the role of low-dose rivaroxaban (≤10 mg daily) for the treatment of atherosclerotic cardiovascular disease (ASCVD). Methods: PubMed, Embase and the Cochrane Library were searched for randomized controlled trials (RCTs) of low-dose rivaroxaban in patients with ASCVD including coronary artery disease (CAD) and peripheral artery disease (PAD). Literature screening, data extraction, and risk of bias assessment were carried out independently by two researchers. Hazard ratio (HR) and 95% confidence interval (CI) were calculated using random-effect models to determine risks of outcomes in ASCVD patients treated with rivaroxaban and comparators, and meta-analysis was conducted via Review Manager 5.3.5 software. Results: 3,768 records were obtained through literature search, and 9 articles representing 6 RCTs ultimately qualified for this study. The meta-analysis indicated that for patients with CAD, the addition of rivaroxaban (5 mg daily) to aspirin could significantly reduce the risk of major adverse cardiovascular events (MACEs) compared with aspirin alone (HR 0.81, 95% CI, 0.72 to 0.91, p = 0.0004, I2 = 60%, 4 studies). For PAD patients receiving rivaroxaban (5 mg daily) plus aspirin, there was no significant reduction in the risk of MACEs (HR 0.84, 95% CI, 0.63 to 1.13, p = 0.25, I2 = 74%, 2 studies); however, there was significant reduction in major adverse limb events (MALEs) (HR 0.54, 95% CI, 0.35 to 0.83, p = 0.005, one studies) and in the composite of MACEs or MALEs (HR 0.78, 95% CI, 0.64 to 0.95, p = 0.02, I2 = 66%, 2 studies) when compared with patients receiving aspirin alone. Meanwhile, rivaroxaban combined with aspirin significantly increased the risk of International Society on Thrombosis and Haemostasis (ISTH) major bleeding compared with aspirin alone in patients with CAD (HR 1.74, 95% CI, 1.43 to 2.13, p < 0.00001, I2 = 0%, 2 studies) and PAD (HR 1.47, 95% CI, 1.19 to 1.83, p = 0.0004, I2 = 0%, 2 studies). Conclusions: Compared with standard antiplatelet therapy, the addition of a 5 mg daily dose of rivaroxaban to standard antiplatelet therapy may improve cardiovascular or limb outcomes of patients with ASCVD, with an increase in major bleeding. Patients who would benefit from the addition of low-dose rivaroxaban to antiplatelet agents and appropriate dual-pathway antithrombotic strategies should be identified in clinical practice to individualize antithrombotic therapy.